Augmented Lagrangian method for a total variation-based model for demodulating phase discontinuities. (July 2020) - Legarda-Saenz, Ricardo; Brito-Loeza, Carlos
In this work, we reformulate the method presented in App. Opt. 53:2297 (2014) as a constrained minimization problem using the augmented Lagrangian method. First we introduce the new method and then describe the numerical solution, which results in a simple algorithm. Numerical experiments with both synthetic and real fringe patterns show the accuracy and simplicity of the resulting algorithm.